2015
DOI: 10.1108/ijrdm-06-2013-0120
|View full text |Cite
|
Sign up to set email alerts
|

Seeking attention: an eye tracking study of in-store merchandise displays

Abstract: Purpose-The purpose of this paper is to elucidate the role that visual measures of attention to product and information and price display signage have on purchase intention. The authors assessed the effect of visual attention to the product, information or price sign on purchase intention, as measured by likelihood to buy. Design/methodology/approach-The authors used eye-tracking technology to collect data from Australian and US garden centre customers, who viewed eight plant displays in which the signs had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 29 publications
9
77
0
5
Order By: Relevance
“…However, until recently, less attention has been given to analyzing the relationship between eye movement and consumer attention to retail product displays (Behe et al, 2013a). Those studies investigated which display attributes had an impact on American and Australian consumers' purchase intention in a retail environment (Huddleston et al, 2013) and consumer product involvement, visual attention and purchase intention (Behe et al, 2013a) Sorensen, Clement, and Gabrielsen (2012) examined the relationships between a product name on a label, participant's level of general food knowledge, and attractiveness of the product. They found that consumers with higher general food knowledge showed longer time to first fixation (TFF) on information and shorter total visit duration (TVD), and that consumers paid attention to sign-post labels early in the search process.…”
Section: Introductionmentioning
confidence: 98%
“…However, until recently, less attention has been given to analyzing the relationship between eye movement and consumer attention to retail product displays (Behe et al, 2013a). Those studies investigated which display attributes had an impact on American and Australian consumers' purchase intention in a retail environment (Huddleston et al, 2013) and consumer product involvement, visual attention and purchase intention (Behe et al, 2013a) Sorensen, Clement, and Gabrielsen (2012) examined the relationships between a product name on a label, participant's level of general food knowledge, and attractiveness of the product. They found that consumers with higher general food knowledge showed longer time to first fixation (TFF) on information and shorter total visit duration (TVD), and that consumers paid attention to sign-post labels early in the search process.…”
Section: Introductionmentioning
confidence: 98%
“…In such circumstances it becomes both a necessity and extremely hard to differentiate itself from competition. Huddleston et al (2015) found that providing signs with product information but without product price elicits higher likelihood to buy than providing signs with price. Furthermore, the authors found a positive relationship between visual attention to price on the display sign and likelihood to buy, but an inverse relationship between visual attention to information and likelihood to buy.…”
Section: Literature Review On the Effect Of Store Attributes On Customentioning
confidence: 98%
“…However, it was determined that attention to products in a display tray was less favourable to products not in a display tray . Ultimately, in recent years, eye tracking has been moving more into the realm of evaluating point‐of‐purchase marketing . Within this area, a study investigated the shelf displays of two products to assess brand consideration .…”
Section: Introductionmentioning
confidence: 99%
“…29 Ultimately, in recent years, eye tracking has been moving more into the realm of evaluating point-of-purchase marketing. 30 Within this area, a study investigated the shelf displays of two products to assess brand consideration. 5 It was found that consumers fixated on price much less often than brand, and they did not note the price if they had not yet noted the brand.…”
Section: Introductionmentioning
confidence: 99%